Conductive thermal ablation of 4T1 murine breast carcinoma reduces severe hypoxia in surviving tumour - Przybyla, Beata D.; Shafirstein, Gal; Koonce, Nathan A.; Webber, Jessica S.; Griffin, Robert J. (International journal of hyperthermia, 2012)
Purpose: The purpose of this study was to quantify hypoxia changes in viable tumour volumes after thermal ablation of a murine breast carcinoma. Methods: Murine breast 4T1 tumours were grown in the rear leg of BALB/c mice to an average diameter of 10-12 mm. Tumours were treated with conductive interstitial thermal therapy (CITT) at a peak temperature of 80-90°C for 10 min. The animals were euthanised 72 h later, and the tumours were removed for immunohistochemical staining with pimonidazole - a marker of partial pressure of oxygen. The levels of pimonidazole staining intensity were used to quantify changes in hypoxia gradients in terms of strong, medium and weak positive pixel fractions. Results: The pimonidazole staining ratio of viable control tumour tissue to viable tissue in tumours that were ablated was 0.7 for weak staining, 2.7 for medium staining and 8.0 (p < 0.03) for strong pimonidazole staining. Conclusion: This shift of pimonidazole staining toward lower intensity pixels in the remaining tumour indicates that tumour ablation with CITT may increase radiosensitivity of the remaining tumour tissue and presents a rationale for combination therapy.